Effects of visible light wavelengths on seed germinability in Stevia rebaudiana Bertoni - Abdullateef, Raji Akintunde; Osman, Mohamad (Canadian Center of Science and Education, 2011)
Stevia rebaudiana Bertoni is one of 154 members of the genus Stevia and it produces sweet steviol glycosides .It originated from Paraguay. The leaves were used as general sweetening agent. Seed germination in Stevia isgenerally very low and constituted major obstacle to large scale production of the crop. Different wavelengths from visible light were tested on germination of Stevia seeds. The two lights used were (i) white light - 400 to 700nm, and (ii) red light - 660nm. Parameters evaluated include (i) Mean time germination, (ii) mean daily germination, (iii) germination rate, (iv) daily germination speed and (v) germination value. Multivariate tests at probability level <.05 revealed that daily germination speed and number of germinated seeds were significantly higher at (< .001) and (< .014) respectively with the effect of red light on seed germination. Red light (660nm) had better influence on germination in Stevia seeds than white light (400-700nm) and control experiment.